1 и 5
Пошаговое объяснение:
0,5|x - 3| = -6 + 7
0,5|x - 3| = 1
|x - 3| = 1 : 0,5
|x - 3| = 2
1) x - 3 = -2
x = -2 + 3
x = 1
2) x - 3 = 2
x = 2 + 3
x = 5
0,5*|x-3|-7=-6
0,5*|x-3|=1
|x-3|=2
Т.к. |2|=2 и |-2|=2, разобьем уравнение на два.
x-3=2⇒х=5
x-3=-2⇒х=1
1 и 5
Пошаговое объяснение:
0,5|x - 3| = -6 + 7
0,5|x - 3| = 1
|x - 3| = 1 : 0,5
|x - 3| = 2
1) x - 3 = -2
x = -2 + 3
x = 1
2) x - 3 = 2
x = 2 + 3
x = 5
0,5*|x-3|-7=-6
0,5*|x-3|=1
|x-3|=2
Т.к. |2|=2 и |-2|=2, разобьем уравнение на два.
x-3=2⇒х=5
x-3=-2⇒х=1